Degradation kinetics and COD fractioning of agricultural wastewaters from biogas plants applying biofilm respirometry. Issue 15 (3rd July 2021) - Cramer, Michael; Schelhorn, Patrick; Kotzbauer, Ulrich; Tränckner, Jens
ABSTRACT: Stormwater runoff from agricultural silo facilities can be heavily polluted and needs to be treated before discharged. This study investigates biological treatability and kinetic constants of characteristic silo runoffs, applying attached growth systems. For this, respirometry measurements, typically applied in the activated sludge systems (ASM) as a suspended growth, were modified by using adapted biofilm carriers. This allows a determination of degradation kinetic of the biofilm system and a COD fractioning at the same time, which are fundamental values for the design of a full-scale plant. The developed respirometry method was compared with the state-of-the-art method using suspended growth systems and domestic wastewater. Results are comparable with the parameter of the ASM. As stormwater runoff is usually a mixture from different pollution sources, various, typically occurring substrates are investigated regarding degradation kinetics and COD fractions. Wastewater polluted with digestion residue and solid manure showed similar COD fractions as domestic wastewater with an inert fraction Si of 5–6% and a comparatively low rapidly degradable fraction SS of 21–27%. However, wastewater from corn or whole crop silage showed significant better degradation efficiencies and kinetics with an Si of 2–3% and a rapidly degradable fraction of 56–57%. As COD concentrations up to 5000 mg L −1 for stormwater runoff and up to 60, 000 mg L −1 for silage effluent can be expected, the results not only show the necessity but also prove the feasibility of biological treatment of stormwater runoff from silo works and provide design parameters for adapted treatment systems. GRAPHICAL ABSTRACT: UF0001